ANALYZING FACTORS THAT DRIVE REPURCHASE INTENTION OF HERBALIFE NUTRITION SHAKE PRODUCT IN MANADO - Moniaga, Yosafat Timotius; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : Herbalife Nutrition through the distributors provided a Nutrition Club that they called a place for breakfast and work out. In Manado, there lots of nutrition Club that has been operated since two years ago. The existence of this club indicates repurchase intention of this particular brand. The object of this study is to define the factors that drive customer intention to purchase Herbalife Shake products in Manado.Â  This research is categorized an associative study and used quantitative method which utilizes confirmatory factor analysis as the tool of analysis. This study obtains primary data and sample is collected from Herbalife Nutrition Club members in Manado. The research results show that Customer Engagement factor, Product quality, Reference group, reliability, promotional, product packaging, tangibility, individual and psychological factor are the contributing factor in affecting the repurchase intention.Keywords : repurchase intention, customer engagement, product quality, reference group, reliability, promotional, product packaging, tangibility, individual, psychological factors.